COVID‐19 pandemic responses of Canada and United States in first 6 months: A comparative analysis. (12th September 2021) - Combden, Shianne; Forward, Anita; Sarkar, Atanu
Abstract: Introduction: Canada and the United States have distinct health care and social policies, and it is important to see how they had been responding to the ongoing COVID‐19 pandemic. Methods: The study period was limited to the first 6 months of the pandemic and aimed to explore the responses by public health authorities, media, general population, and law makers during the initial phase of pandemic. Results: Social disparity, underfunded pandemic preparation, and the initial failure to act appropriately have resulted in the rapid spread of infection in both countries. In the United States, prevailing social inequalities and racism, inaccessible health care, higher rates of preexisting medical conditions and disputed political leadership have further deteriorated the situation and enhanced public suffering, particularly for the black and Indigenous communities. In Canada, its poorly regulated services of long‐term care facilities, initial restriction of testing and lack of access to epidemiological data have helped spread the infection and increased casualties in vulnerable populations. Conclusion: Analysis of the pandemic responses of the United States and Canada has revealed how existing social disparity, underfunded pandemic preparation, and the initial failure to act appropriately have resulted in the rapid spread of infection.